Becoming a runner: big, middle and small stories about physical activity participation in later life. Issue 1 (2nd January 2016) - Griffin, Meridith; Phoenix, Cassandra
Abstract : How do older adults learn to tell a 'new' story about, through, and with the body? We know that narratives are embodied, lived and central to the process of meaning-making—and as such, they do not lie in the waiting for telling, but are an active part of everyday interaction. Telling stories about ourselves to others is one way in which our identity may be performed, and is intricately connected to the social contexts within which it occurs. Narrative analysis, therefore, requires attention to stories told in both structured research settings as well as within everyday talk and interaction. Drawing upon data generated during a 14-month ethnography of a women's-only running group in the UK, we use the concepts of 'big stories', 'middle stories' and 'small stories' as an analytical framework to demonstrate the dynamic nature of identity and narrativity in context [Bamberg, M. (2006). Biographic-narrative research, quo vadis ? A critical review of 'big stories' from the perspective of 'small stories'. In K. Milnes, C. Horrocks, B. Roberts, & D. Robinson (Eds.), Narrative, memory and knowledge: Representations, aesthetics and contexts (pp. 63–79). Huddersfield: University of Huddersfield Press; Bell, N. J. (2009). Making connections: Considering the dynamics of narrative stability from a relational approach. Narrative Inquiry, 19 (2), 280–305; Freeman, M. (2006). 'Life "on holiday"? In defense of big stories.' Narrative Inquiry, 16 (1), 131–138; Georgakopoulou, A. (2006). Thinking big with small stories in narrative and identity analysis. Narrative Inquiry, 16 (1), 122–130]. Alongside examples of stories in each dimension, we untangle the complexity of becoming active for mid- and later life participants. We discuss the analytical possibilities of taking a relational approach to narrative analysis, changing the focus from the (oft studied) structural properties of narrative to narration as a process [De Fina, A., & Georgakopoulou, A. (2008). Analysing narratives as practices. Qualitative Research, 8 (3), 379–387; Sools, A. (2013). Narrative health research: Exploring big and small stories as analytical tools. Health: An Interdisciplinary Journal for the Social Study of Health, Illness & Medicine, 17 (1), 93–110]. In doing so, we explore the 'hows' of identity change (or narrative identity creation)—offering insight into complex and shifting body–self relationships and their accompanying uncertainties, ruptures and discontinuities.